Translators as Well as Thinkers: Teaching of Journalistic Translation in Hong Kong - Li, Defeng (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractHong Kong is probably one of the most exciting places in the world to study translation as a student or a researcher. Seven out of the eight universities offer translation degrees. Among others, journalistic translation has always been one of the most popular courses for students. However, students have often felt underprepared in journalistic translation even after taking some related courses. This study argues, with the support of empirical evidence that one of the major reasons accountable for this is the gap between institutional translator training and the real world of professional translation, which, in the context of journalistic translation, manifests itself as the difference in translation methods taught in translation programs and used in professional practice. The author further contends that this gap needs to be bridged in order to better prepare student translators for the market. Recommendations are also made as to how the gap can be narrowed or bridged.